TEACHING VOCABULARY IN CONTEXTUALIZATION FOR YOUNG LEARNERS - Irwandi Irwandi; Gusti Milla Quaidy; Albert Albert (Universitas Negeri Padang, 2018)
The primary focus of this study is to determine the effect of teaching vocabulary in contextualization for young learners. Vocabulary is one of the central components in a language included in English. According to Luppescu and Day (1993: 266),